PENGARUH PENERAPAN MEDIA AUDIO VISUAL DAN MEDIA KOMIK TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN SKI KELAS X MAN PANGKEP - Yusuf, M (Inspiratif Pendidikan, 2019)
The study discussed the influence of the implementation of audio visual and comic media on the improvement of students' learning outcomes in learning the History of Islamic Culture of Class X MAN Pangkep. The study was aimed at: (1) describing the implementation of audio visual media positively influenced the students’ learning outcomes in learning the History of Islamic Culture of Class X MAN Pangkep, (2) describing the implementation of comic media positively influenced the students’ learning outcomes in learning the History of Islamic Culture of Class X MAN Pangkep, (3) describing the differences of the influence between audio visual media and comic media on the students’ learning outcomes in learning the History of Islamic Culture of Class X MAN Pangkep. The study was quantitative quasi experimental research having a controlled group, but did not fully control the variables influencing the experiment implementation. Methodological and scientific approaches were utilized in this study. The population was all class X students of MAN Pangkep as many as 270 people whom 24 of them were taken as the samples of class X MIA 1 using a purposive sampling technique. Multiple choice test, observation and documentation were applied as research instruments to gather the data which then analyzed using descriptive and inferential statistical analysis techniques. Based on the results of descriptive data analysis, it was obtained the average score of both groups, namely the pretest and posttest of the controlled class were 71 and 83 respectively, while 72 and 85 for the experimental class. Based on the results of inferential statistical analysis, it was obtained the tcount = 1.95 and the value of the ttable with α = 0.55 and dk = (12+12-2) = 22 was 2.17. Since the tcount < ttable (1.95 < 2.17), it can be concluded that Ho was rejected and Ha was accepted, this means that there was an average difference of learning outcomes between class taught using audio-visual media and that using comic media on the students’ learning outcomes of the History of Islamic Culture of Class X MAN Pangkep.